Optimization of Counseling Services at the Desks to the Four Posyandu - Novi Indrayani (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Introduction: Health counseling activities at the fourth table in posyandu services are still a serious problem. Counseling can detect early problems in babies and toddlers. Counseling services have not been carried out regularly at this posyandu. The purpose of this community service is the empowerment of cadres to improve posyandu services at the fourth table (counseling services) using posyandu counseling back sheet tools. Methods: The method used by providing education on counseling back sheets to posyandu cadres. The data collection technique is the observation of cadre counseling using counseling back sheets and pre-tests and postests to measure maternal satisfaction. The instruments used are in the form of checklists and questionnaires. The population at this service is 6 cadres and 31 mothers of babies and toddlers. The sampling technique uses total samples. The data analysis used is the percentage and mean formulas. The Location of Service at Posyandu Lestari I and Posyandu Ringin I in the Prambanan Puskesmas Work Area will be carried out in October 2022 with 3 hours of activity. Results: The results obtained were the average score of the implementation of cadre counseling using the counseling feedback sheet. The results of the posyandu service survey before and after the mother received counseling services from posyandu cadres, namely 54.8% in the dissatisfied category. After receiving counseling, the posttest score was mostly 83.9% in the satisfied category. Conclusion: These results show that posyandu counseling education with back sheet tools can improve posyandu services, especially in the 4th table. The devotee hopes there will be further empowerment activities to optimize services at the posyandu, one of which is technical training in counseling.